Determining the performance of five multiple choice scoring methods in estimating examinee's ability / Lau Sie Hoe … [et.al.]. - Lau, Sie Hoe; Ngee Kiong, Paul Lau; Ling, Siew Eng; Tee Yong, Hwa (2006)
Despite the current popularity of performance-based assessment and the emergence of new assessment methods, multiple choices (MC) item remain a major form of assessment. Conventional Number Right (NR) scoring method where one point for correct response and zero for other response has been consistently criticized for failure to credit partial knowledge and encourage guessing. Various alternative scoring methods such as Number Right with Correction for Guessing (NRC), Elimination Testing (ET), Confidence Weighting (CW) and Probability Measurement (PM) had been proposed to overcome these two weaknesses. However to date, none has been widely accepted although the theoretical rationale behind various scoring methods under Classical Test Theory (CTT) is sound. A major cause of concern is the possibility that complicated scoring instruction might introduce other factors, which may affect the reliability and validity of the test scores.